Penduduk dan pertumbuhan ekonomi di Indonesia: Analisis kausalitas - Agus Widarjono (Universitas Islam Indonesia, 1999)
Impact of population on economic growth had been questioned a long time ago, Classical economist, Adam Smith, emphasizes that high rate of population growth would support economic growth through specialization and division of labor. In other hand, Thomas R. Mathus, another classical economist, emphasizes the negatives effect of population investment rate and in turn results in a lower of economic growth.